The Effectiveness Of The Partnership Strategy Between Hotel Borobudur Jakarta And Art Education Institutions In The Effort To Preserve Traditional Indonesian Arts And Culture - Taris Zakira Alam; Hoga Saragih (Yayasan Riset dan Pengembangan Intelektual, 2026)
Competition in the modern hotel industry no longer relies solely on price, physical facilities, and service quality, but rather on differentiation strategies that create experiential value through intangible, authentic, and sustainable values. Leveraging culture as a strategic resource is a relevant approach to building a competitive advantage that is difficult to imitate. This research examines the cultural partnership undertaken by Hotel Borobudur Jakarta through the Discover Art & Batik program (October 2025) with the Jakarta Arts Institute, Digitalcom Academy, Jakarta State University, and Betawi painting maestro Sarnadi Adam. This partnership is positioned not as a ceremonial activity, but as a culture-based management strategy integrated with branding, CSR, and Creating Shared Value (CSV). The Discover Art & Batik program, which features traditional regional dances, seminars on Indonesian cultural writing, traditional Indonesian music, Betawi painting workshops, and Betawi painting exhibitions, represents the implementation of a non-financial differentiation strategy that leverages cultural value as a value-added business strategy. Within a strategic management framework, this activity demonstrates how culture can be ethically capitalized on as a source of competitive advantage without losing the essence of preserving traditional values. Using a grounded theory approach (open, axial, selective coding), the research focuses analysis on three main managerial aspects: (1) the challenges of cross-institutional partnerships, (2) partnership management strategies, and (3) the impact of partnerships on the organization. The results indicate that cultural partnerships function as a non-financial differentiation strategy that strengthens brand identity, brand equity, institutional reputation, and social legitimacy, while also supporting the preservation of traditional Indonesian culture. This study fills the research gap regarding hotel-arts institution partnerships as a sustainable management and branding strategy. The findings provide theoretical and practical contributions to the study of strategic management, partnership management, cultural-based branding, CSR, and CSV by positioning arts and culture as strategic resources within modern organizations.